Sexual Objectification of Girls in Anime Series: Sara Mills’ Critical Discourse Analysis - Hutagalung, Sandra; Maryani, Eni; Setiaman, Agus (Lingkar Studi Komunikasi (LISKI), 2024)
The "sex sells" marketing strategy is still used by anime, a form of entertainment that is becoming more and more popular worldwide, and one of them is Mushoku Tensei: Isekai Ittara Honki Dasu anime series. Due to the main character's vulgarity against girls, this anime series sparked debate among anime viewers. For a number of reasons, such as the freedom to work for artists and the fact that sexual objectification done through animation does not damage real girls, objections to this topic are frequently refuted. The goal of this study is to identify the various ways that girls are sexually objectified in anime, which could affect viewers' attitudes and actions. A qualitative approach is used through critical discourse analysis by Sara Mills. Discourse is utilized methodologically to dismantle forms of sexual objectification of women in anime series. It is revealed how women are portrayed as sexual objects in anime fan service through the male gaze through discourse analysis of characters, focalization, fragmentation, and cinema schemata. Findings from this study indicate that there existed instances of sexual objectification of women in the anime series Mushoku Tensei: Isekai Ittara Honki Dasu, particularly in relation to the love interest of the main male character. This study critically makes us aware that the growth of digital media, which can provide a wide range of content and depict a variety of male and female characters, nevertheless reinforces patriarchal value. Even in the digital age, animation—a creative form of entertainment—continues to treat girls as just objects of desire for men. This serves as a reminder that the conventional entertainment industry, which frequently makes fun of sexual harassment of women, still exists in the internet sphere. In light of this anime series, women participation in the digital sphere ought to be promoted in order to change people's perceptions of women. It has been proven that the freedom that many advocate in the digital age yet imposes restrictions on the presence of girls as a subject. Keywords: anime; digital; girls; objectification; male gaze;